The management of linguistic and cultural minorities in a national state - Bussotti, L. (Problems of Management in the 21st Century, 2016)
This short reflection aims to present how Italy has managed the linguistic and cultural differences inside its national territories, considering three fundamental historical steps: the first period of unification; the Fascism; the period after the end of the Second World War, culminating in the approval of the first organic law that protects its historical linguistic minorities.